Intellectual Property Rights as Fiduciary Collateral in Indonesian Legal Framework - Lailatul Farochah; Abdul Rokhim; Ahmad Syaifudin (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Intellectual Property Rights have evolved from moral recognition instruments into economically valuable intangible assets within modern legal systems. Specific Background In Indonesia, positive law has formally recognized Intellectual Property Rights as movable intangible objects eligible for fiduciary security through Law No. 42 of 1999 and Government Regulation No. 24 of 2022, particularly within the creative economy sector. Knowledge Gap Despite normative recognition, significant obstacles remain in valuation mechanisms, institutional readiness, and execution procedures, limiting practical utilization of Intellectual Property Rights as fiduciary collateral. Aims This study aims to examine the legal construction of Intellectual Property Rights as fiduciary objects and to analyze the legislative rationale for such classification using Richard A. Posner’s Economic Analysis of Law approach. Results The findings demonstrate that Intellectual Property Rights satisfy property law criteria as fiduciary objects due to their economic value and transferability, yet Indonesia’s fiduciary system exhibits structural inefficiencies, especially in asset appraisal and enforcement certainty. Novelty This research integrates Indonesian fiduciary law with Posner’s efficiency-based legal theory to explain the normative justification of Intellectual Property Rights as bankable collateral. Implications The study highlights the need for regulatory synchronization, institutional reform, and valuation infrastructure to support Intellectual Property–based financing aligned with principles of legal certainty and economic efficiency. Highlights: Indonesian positive law categorizes intangible rights with economic value as fiduciary objects. Valuation and execution uncertainty constrains acceptance of intangible collateral by financial institutions. Efficiency-based legal reasoning supports collateralization of non-physical economic assets. Keywords: Intellectual Property Rights, Fiduciary Security, Economic Analysis of Law, Creative Economy, Legal Certainty